2012
DOI: 10.5194/cp-8-415-2012
|View full text |Cite
|
Sign up to set email alerts
|

Climatically-controlled siliceous productivity in the eastern Gulf of Guinea during the last 40 000 yr

Abstract: Abstract. Opal content and diatom assemblages were analysed in core GeoB4905-4 to reconstruct siliceous productivity changes in the eastern Gulf of Guinea during the last 40 000 yr. Opal and total diatom accumulation rates presented low values over the considered period, except during the Last Glacial Maximum and between 15 000 calendar years Before Present (15 cal. ka BP) and 5.5 cal. ka BP, the so-called African Humid Period, when accumulation rates of brackish and freshwater diatoms at the core site were hi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 72 publications
(119 reference statements)
1
33
1
Order By: Relevance
“…The marine diatom community is dominated by coastal planktonic and brackish species. Coastal planktonic diatoms thrive in neritic, oligo‐to‐mesotrophic waters with high to moderate dissolved silica levels, becoming more abundant during intervals of weak turbulence and responding mainly to moderate upwelling (Romero and Armand, ; Crosta et al , ). Main components of the brackish group mostly live attached to a substratum as epipelic, epiphytic or epizoic diatoms.…”
Section: Resultsmentioning
confidence: 99%
“…The marine diatom community is dominated by coastal planktonic and brackish species. Coastal planktonic diatoms thrive in neritic, oligo‐to‐mesotrophic waters with high to moderate dissolved silica levels, becoming more abundant during intervals of weak turbulence and responding mainly to moderate upwelling (Romero and Armand, ; Crosta et al , ). Main components of the brackish group mostly live attached to a substratum as epipelic, epiphytic or epizoic diatoms.…”
Section: Resultsmentioning
confidence: 99%
“…Cyst assemblages were determined by light microscopy (Zeiss Axiovert, 400× magnification). The taxonomy of calcareous dinoflagellate cysts follows Vink et al (2002) and Elbrächter et al (2008), while that of organic-walled dinoflagellate cysts is according to Zonneveld and Pospelova (2015).…”
Section: Calcareous and Organic-walled Dinoflagellate Cystsmentioning
confidence: 99%
“…The surface sediment at 22 • W just east of M1 also reveals the highest diol index (0.22), likely due to its closer vicinity to the Guinea Dome center. Several studies have reported P. alata diatoms offshore of northwest Africa (Lange et al, 1998;Treppke et al, 1996;Crosta et al, 2012;Romero et al, 1999), pointing to P. alata as a plausible source organism. The sedimentary annual diol indices compare well with the sediment trap indices (Fig.…”
Section: Lcd Sources and Seasonalitymentioning
confidence: 99%